MicroMandarin: Mobile Language Learning in Context - Edge, Darren; Searle, Elly; Chiu, Kevin; Zhao, Jing; Landay, James A. (CHI 2011 Conference on Human Factors in Information Systems, 2011)
Learning a new language is hard, but learning to use it confidently in conversations with native speakers is even harder. From our field research with language learners, with support from Cognitive Psychology and Second Language Acquisition, we argue for the value of contextual microlearning in the many breaks spread across different places and throughout the day. We present a mobile application that supports such microlearning by leveraging the location-based service Foursquare to automatically provide contextually relevant content in the world’s major cities. In an evaluation of Mandarin Chinese learning, a four-week, 23-user study spanning Beijing and Shanghai compared this contextual system to a system based on word frequency. Study sessions with the contextual version lasted half as long but occurred in twice as many places as sessions with the frequency version, suggesting a complementary relationship between the two approaches.